Digital twin for multi-scenario emergency of railway passenger stations - Wang, Xiaoshu; Bai, Wei; Su, Yuanqi; Yang, Guoyuan; Li, Chao; Lv, Xiaojun; Peng, Kaibei; Li, Jun (Frontiers in Physics, 2024)
Emergency disposal is a critical aspect for railway stations to ensure safety. This requires the implementation of emergency plan simulations and cost-effective immersive drills. In the paper, we incorporate a set of disposals for events into emergency processes and model the personnel, supplies, and equipment to create multiple emergency scenarios. Additionally, we introduce a digital twin-based solution for multiple scenarios of emergencies. This solution completely restores the key components of a station in the information space and provides an immersive way for emergency disposals. The four-dimensional model used in the solution simulates and interacts with the station, and it is composed of the details of passenger station physical entity, multiscenario emergency virtual entity, digital twin connection, and emergency twin service. The digital twin for versatile emergency events such as fire disaster, natural disaster (e.g., flood, earthquake), social security incident, and public health event have been constructed using the model. The solution was tested at Qinghe, a station during Beijing-Zhangjiakou high-speed railway in China.By utilizing the actual operation data of Qinghe, we validated the multi-scenario emergency drills, simulated the corresponding emergency disposal plans, and assessed the proposed solution from three aspects: the fidelity of the real-world simulation, coverage of the multiple emergency scenarios, and the user-friendliness. The evaluations indicate that the proposed solution attains good score and the acceptable level of system usability scale.